2022
DOI: 10.1017/mor.2022.1
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Socioemotional Wealth: Social Wealth and Emotional Wealth as Core Properties of Family Firms

Abstract: The concept of socioemotional wealth (SEW) has become a dominant perspective in family business studies. In this article, we review the SEW literature, the explanatory power of SEW in family firm behavior, and the heterogeneity of family firms. Although we find that SEW distinguishes the behavior of family firms from that of nonfamily firms, the concept has been used and operationalized differently across studies. The few studies that measure SEW directly do not find clear and consistent explanatory power of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 89 publications
1
13
0
Order By: Relevance
“…Also, this study found that when the financial condition of family business is poor, the impact of regional culture on local family businesses is more pronounced. The existing studies often believe that there is a diminishing marginal effect of economic versus psychological returns for family firms ( Miller and Le Breton, 2014 ), i.e., when family firms have already obtained generous economic returns, they will focus more on acquiring psychological returns, and when economic returns are insufficient, they will temporarily weaken their pursuit of psychological returns and focus on economic returns instead ( Chen et al, 2022 ). The findings of this study, however, indicate that when the financial condition of family business is poor, the differences in the importance attached to psychological returns is more pronounced between family firms in areas where clan culture is prevalent and those in areas where clan culture is indifferent.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this study found that when the financial condition of family business is poor, the impact of regional culture on local family businesses is more pronounced. The existing studies often believe that there is a diminishing marginal effect of economic versus psychological returns for family firms ( Miller and Le Breton, 2014 ), i.e., when family firms have already obtained generous economic returns, they will focus more on acquiring psychological returns, and when economic returns are insufficient, they will temporarily weaken their pursuit of psychological returns and focus on economic returns instead ( Chen et al, 2022 ). The findings of this study, however, indicate that when the financial condition of family business is poor, the differences in the importance attached to psychological returns is more pronounced between family firms in areas where clan culture is prevalent and those in areas where clan culture is indifferent.…”
Section: Discussionmentioning
confidence: 99%
“…As far as controlling families are concerned, family firms must not be short-term disposable assets but rather a source of the family's heritage, which is an integral component of SEW (Strike et al, 2015;Swab et al, 2020). Family heritage is unique to the controlling families because it is based on kinship and trust among family members; thus, it is difficult for nonfamily firms to match family firms' level of SEW (Davis et al, 2010;Chen et al, 2022). For this reason, controlling family members aspire to intergenerational CEO succession within the family, which reinforces family bonds and enables the family to control the firm for generations (Chung and Yuen, 2003;Gomez-Mejia et al, 2011).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Family heritage is unique to the controlling families because it is based on kinship and trust among family members; thus, it is difficult for nonfamily firms to match family firms' level of SEW (Davis et al. , 2010; Chen et al. , 2022).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…In their theoretical piece, entitled 'Deconstructing Socioemotional Wealth: Social Wealth and Emotional Wealth as Core Properties of Family Firms', Chen, Zhou, Zhou, Hofman, and Yang (2022) provided a thorough literature review on socioemotional wealth (SEW), one of the key concepts in family business research. A remarkable contribution of this study is that the authors make a conceptual distinction between emotional wealth, i.e., the satisfaction of family members' affective needs, and social wealth, which refers to family business reputation, organizational identification, and social capital.…”
Section: Papers In This Issuementioning
confidence: 99%
“…Groundbreaking research means to stimulate future studies that challenge, expand, and extend the theory and findings of the current study. Chen et al's (2022) theoretical analysis does more in this regard, especially their final point on how to incorporate contextual factors into their theoretical framework, although more elaboration is desirable. Furthermore, the intersection of economic, social, and political forces, in conjunction with their current typology, may help develop testable hypotheses.…”
Section: Future Research Agendamentioning
confidence: 99%